Probiotic Exopolysaccharide Protects against Systemic Staphylococcus aureus Infection, Inducing Dual-Functioning Macrophages That Restrict Bacterial Growth and Limit Inflammation - Paik, Wonbeom (Infect Immun, 2018)
Staphylococcus aureus causes severe systemic infection with high mortality rates. We previously identified exopolysaccharide (EPS) from a probiotic, Bacillus subtilis, that induces anti-inflammatory macrophages with an M2 phenotype and protects mice from Citrobacter rodentium-induced colitis. We tested if EPS could protect from systemic infection induced by S. aureus and found that EPS-treated mice had enhanced survival as well as reduced weight loss, systemic inflammation, and bacterial burden. While macrophages from EPS-treated mice display an M2 phenotype, they also restrict growth of internalized S. aureus through reactive oxygen species (ROS), reminiscent of proinflammatory phagocytes. These EPS-induced macrophages also limit T cell activation by S. aureus superantigens, and EPS abrogates systemic induction of gamma interferon after infection. We conclude that B. subtilis EPS is an immunomodulatory agent that induces hybrid macrophages that bolster antibacterial immunity and simultaneously limit inflammation, reducing disease burden and promoting host survival.